2017
DOI: 10.1111/lam.12784
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteome, antigen protein and antigen membrane protein fromSpiroplasma eriocheiris

Abstract: Spiroplasma eriocheiris is a novel pathogen causing the tremor disease in Chinese mitten crab Eriocheir sinensis. This is the first time LC-MS/MS was used to identify the proteome, antigen protein and antigen membrane protein of S. eriocheiris. The results can certainly provide valuable information towards the identification of virulent proteins or diagnosis of pathogenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Moreover, heat shock protein 70, pyruvate dehydrogenase E1‐beta subunit, elongation factor Tu and the P76 membrane protein of Mycoplasma hyopneumoniae were determined as antigenic protein (Pinto et al, ). The SPE0313 protein is proved as membrane antigenic protein of S. eriocheiris by proteomics analysis (Liu et al, ), but its characteristics and functions were not studied clearly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heat shock protein 70, pyruvate dehydrogenase E1‐beta subunit, elongation factor Tu and the P76 membrane protein of Mycoplasma hyopneumoniae were determined as antigenic protein (Pinto et al, ). The SPE0313 protein is proved as membrane antigenic protein of S. eriocheiris by proteomics analysis (Liu et al, ), but its characteristics and functions were not studied clearly.…”
Section: Resultsmentioning
confidence: 99%
“…Except adhesion‐like protein ALP, spiralin‐like protein SLP25 and SLP31 were immunoproteins (Meng, Gu, Bi, Ji, & Wang, ; Meng, Ou et al, ), lysophospholipase protein from S. eriocheiris lied in membrane and cytoplasm, the virulence ability was decreased obviously through antibody neutralization test (Zhu et al, ). SPE0313 is an antigenic membrane proteins of S. eriocheiris (Liu et al, ), but the function of SPE0313 in adhesion and invasion of E. sinensis were not clear. Since UGA is not a termination signal but reads as a tryptophan codon in mollicute (Citti, Maréchaldrouard, Saillard, Wei, & Bové, ; Stamburski, Renaudin, & Bové, ), SPE0313 has been site‐muted to express the whole protein in Escherichia coli after gene clone.…”
Section: Introductionmentioning
confidence: 99%
“…PK can catalyze phosphate group transfer and phosphoenolpyruvate conversion to adenosine diphosphate [51, 52]. PK not only takes part in carbohydrate metabolism [5355] but is also involved in immunological reaction progress in crustaceans [56, 57]. A study on Drosophila suzukii found that photoperiod could regulate the PK levels, and then mediate the adult reproductive diapause [58].…”
Section: Discussionmentioning
confidence: 99%
“…After washing and resuspension, the sample was sonicated on ice and centrifuged to remove the cellular debris. Rabbit antiserum against S. mirum was prepared by following the methods described by Liu Y. et al (2017) . The serum was conjugated to Protein A Beads at 4°C for 4 h with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoproteomics as an emerging field of proteome analysis plays a key role in screening immunogenic proteins. Such a method has been used to successfully identify antigenic epitopes in several pathogens, such as Mycoplasma bovis , Brucella abortus , Neisseria meningitidis , and S. eriocheiris ( Liu Y. et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%